Governance of Indian State Power Utilities : An Ongoing Journey - Pargal, Sheoli (Washington, DC: World Bank Group, 2014)
By the late 1990s, the technical and financial performance of the power sector in India had deteriorated to the point where the Government of India had to step in to bail out the state utilities, almost all of which were vertically integrated state electricity boards (SEBs). Considering that the dismal performance of state utilities reflected internal and external shortfalls in governance, the new Electricity Act of 2003 (EA 2003) mandated the unbundling and corporatization of the SEBs, along with the establishment of independent regulators. This was expected to bring about a more accountable and commercial performance culture, with concomitant results in improved utility performance. The rest of this review is organized as follows. Chapter two summarizes the institutional context and relevant developments over the past two decades. Chapter three focuses on the corporate governance agenda adopted by the government and its implementation, specifically relating to the structure and functioning of utility boards of directors. Chapter four reviews SERC regulatory governance. Chapter five analyzes the correlation between key indicators of the quality of regulatory and corporate governance and utility financial performance. And chapter six concludes.